Corpos à deriva e o desejo de filhos: uma análise discursiva sobre o corpo solidário no Brasil - Dullius, Thailline (2025)
Based on theoretical assumptions of French Discourse Analysis, this work aims to investigate how the solidary body (Viana, 2017) is discursivized on the portals of g1 and Folha, digital versions of the newspapers O Globo and Folha de S.Paulo, respectively, and which constitute reference media, since they act as consensus-makers among the population, according to Mariani (1998). The research question that drives us is: how do women who "lend" their bodies to carry a child for another family signify themselves and are signified in/by digital journalistic discourse? More specifically, we seek to understand: a) how digital journalism contributes to crystallizing or disrupting deeply rooted meanings about the female body and the "gestation surrogacy" envisioned by the Federal Council of Medicine (CFM) or "surrogate motherhood," the term most commonly used in our social formation and also by the mass media; b) to map how the Church and medicine collaborated in the process of training/domestication (Del Priore, 2009) of the female body from prehistory to Portuguese colonization. This time frame is justified by its attempt to investigate how the meanings about the female body inherited from the colonizers were constituted and sedimented over time; c) to discuss prohibited or interdicted discourse as that which, for ideological, social, or institutional reasons, cannot circulate freely, highlighting the conflicts and disputes over meaning in society and demonstrating that discourse is always permeated by power relations. It is in this sense that we observe the erasure of the term "surrogate mother" in the corpus selected for analysis. The back and forth between theory and practice allowed us to affirm that surrogacy, provided for by law in some countries, constitutes an efficient means for parents who cannot conceive and/or carry children. Whenever it occurs, it gains significant media visibility, even acquiring the status of a spectacle, reinforcing the notion that to be a mother, one need not bear a child. Enter, then, the woman, who, out of altruism or financial reasons, decides to lend her womb/belly to carry the child. At this point, we address the shattering of the myth of maternal love, proposed by Badinter (1985), according to which motherhood is not something natural to all women, but a historical construct. It was along this path that we began to analyze the discourses that (re-)produce hegemonic discourses about "being a mother," as well as gestures of resistance, which allowed us to title, as part of the title of this research, "Bodies adrift and the desire for children." Ultimately, we understand that the woman's body is traversed by flaws and deficiencies, as is the process of subjectivation of subjects, who, on the one hand, desire children but cannot conceive them, and, on the other, by supportive bodies, which, through an altruistic gesture, seek to fill this lack.